Harmful Gases Profiling in Meru Menora Tunnel using SICK Sensor - A. N. Baharun; N. A. Murad; N. N. N. A. Malik (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper discusses the study on the measured harmful gases due to traffic emission in the Meru Menora Tunnel, a Malaysia highway tunnel. The hazardous gasses data would help in promoting essential ventilation system inside the tunnel for the health and safety of the users. The emission gasses concentration reading is divided into two main components comprise of Nitrogen Dioxide (NO2), and Carbon Monoxide (CO). Other than that, the visibility also been measured by using SICK sensor. The measurement has been done during normal, festive and school holiday seasons. Festive season shows the highest number of traffic and thus giving the worst air quality. Ventilation fan system can be activated based on the concentration level of gases and visibility in the tunnel.